Study of relationship between Environmental Consciousness and Green Purchasing among Youth - Bhati, Bharat; Shukla, R. K. (Gyan Management Journal, 2021)
India is a second largest population in the world and every seventh individual of the world lives in India.16% of the world’s population reside in India but only 2.4% of its land area.Now a day human are consuming natural resources in an unsustainable way. The much needed impetus to industrial development has resulted in huge residuals, having undesirable effects on the environment — air, water and land, disproportional to their contribution to overall economic growth.Globally, People have beenmore aware of environmental issues in last couple of years. Many consumers now express concern about environmental deterioration. This paper studied theEnvironmental Consciousness and Green Purchasing Decisions of Youth. In order to achieve the objectives of the study primary and secondary data has been collected andan in-depth literature review and empirical research were undertaken. A self-administered questionnaire was filled by 124 respondents in which both gender male and female are equal. Through the data analysis and interpretation, it was found that College going students have good knowledge about environmental issues and shown seriousness for environment protection. Accordingly, Green purchasing of students was found influenced.